Bridging the gap between domain of research and locus of impact: An examination of the UK's Research Excellence Framework. Issue 4 (14th May 2018) - Rao-Nicholson, Rekha; Rodgers, Peter; Khan, Zaheer
Abstract : Purpose: The purpose of this paper is to examine the relevance of academic research in the business and management studies stream to various stakeholders. The stakeholder theory is used to examine the influence of research on various key beneficiaries and investigate the link between the domain of research and locus of impact. Design/methodology/approach: Research Excellence Framework 2014 (REF 2014) conducted in the UK provides a useful context and data for our research as REF 2014 encouraged universities to submit the information on research activities and their beneficiaries. This information is in the form of impact case studies which details the research, location of research and beneficiaries. Findings: The findings suggest that research with an international focus has a positive impact on industry stakeholders, especially multinational corporations as well as non-governmental organizations. Second, it shows how research has made a commercial impact in innovation and small and medium enterprises' growth while having limited impact on other domains such as social, legal, political and healthcare. More broadly, the findings indicate the degree of regional diversity. Also, the wider results-driven agenda in the UK can overestimate the research contribution to some stakeholders in the society. Research limitations/implications: Self-selection bias as universities might submit only few case studies. Practical implications: For research to generate long-term benefits for the wider society, it needs to engage more deeply with the whole range of stakeholders. Originality/value: This study contributes to understanding how research is consumed by stakeholders. The results indicate that while locally relevant research encourages local consumption; it is not assimilated across various stakeholders.